The Effects Of Auto-Tuned Method In Pid And Pd Control Scheme For Gantry Crane System - Syed Hussien, Sharifah Yuslinda; Jaafar, Hazriq Izzuan; Ghazali, Rozaimi; Abdul Razif, Nur Rafiqah (2015)
Gantry crane system is a mechanism in heavy engineering that moves payload such container from one point to another. Generally, experienced operators or experts are required to control manually the gantry position while minimizing the payload vibration or swing oscillation. Therefore, those manpower has to be trained in order to operate the gantry crane system safely and efficiently. Thus, to overcome this problem, a feedback control scheme has been utilized in the system. In this paper, PID and PD controllers are introduced for controlling the trolley displacement and the swing oscillation in the gantry crane system. PID controller is designed for tracking the desired position of the trolley whereas PD controller is implemented to minimize the payload oscillation. The PID and PD parameters are tuned by the auto-tuning method. Simulation results have demonstrated satisfactory response based on control system performances.